Associations between anthropometry, body composition, and body image in athletes: a systematic review - Webb, M. D.; Melough, M. M.; Earthman, C. P.; Katz, S. E.; Pacanowski, C. R. (Frontiers in Psychology, 2024)
Introduction Poor body image is a potent risk factor for disordered eating and eating disorders. Athletes are a population at increased risk for eating disorders despite reports of lower body image concerns compared to non-athletes. Body size and composition may influence an athlete`s susceptibility to poor body image.